Understanding of indonesian student behavior and character in english language teaching contexts: a qualitative ethnographic investigation - Farikah, Farikah; Rachmawati, Umi; Widiyanto , Delfiyan; Hananto, Ipung; Jendriadi, Jendriadi; Pradita, Linda Eka (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This qualitative ethnographic study investigates the value of character education for children at elementary school in the context of English Language Teaching and how it affects their emotional growth. The research aims to evaluate several key student behaviour and character indicators, including values, morality, attitudes, interests, and self-concept. Data was collected through direct observation, in-depth interviews, and questionnaire analysis. The results show that students' variances in these indicators provide insight into the range of affective development that occurs in the setting of schooling. The results revealed that most students demonstrated good attitudes, interests, and values, with most rated 'Excellent' or 'Good' in these indicators. However, self-concept showed more significant variation, with several students rated 'Fair'. Moral indicators also show positive results, with most students rated 'Excellent' or 'Good'. This study offers insightful information about students' conduct and personality in learning environments. The findings highlight the need for targeted interventions to improve self-concept and suggest that fostering a supportive and engaging learning environment is crucial for overall character development. These insights can serve as a basis for creating more effective educational programs and improving student performance in learning environments.